Literature Review: Physical Stability Evaluation of Various Natural Extract-Based Preparations - Ines Septiani Pratiwi; Retno Wahyuningrum; Ika Lismayani Ilyas; Auliah Usman; Putri Ramadani Ridwan; Mirna; Zafirah Sarif; Nur Fadilah; Ildhy Alzari Ashar; Shintya Dewi Pratiwi; Anisa Ramadhani; Infahna; Syalda Syahifni Rum (Universitas Muhammadiyah Palu, 2026)
This literature review examines the physical stability of various natural extract-based preparations increasingly used in cosmetic and pharmaceutical formulations. The main problem identified is the high phytochemical variation of the extracts, which can affect physical stability, such as changes in pH, viscosity, homogeneity, color, and texture during storage. The purpose of this study was to analyze physical stability parameters in various dosage forms, such as liquid, semi-solid, and solid, and to evaluate factors influencing their instability, based on selected literature from 2020 to 2025. The method used was a literature review through an online search of national and international journals relevant to the available data. Ten articles were used to support this literature review. The results of the literature review indicate that liquid dosage forms tend to be susceptible to organoleptic and clarity changes, while semi-solid dosage forms are strongly influenced by the stability of polymer matrices and emulsions, while solid dosage forms have the best stability due to their low water content. Based on the results of this literature review, it can be concluded that the physical stability of a preparation is highly dependent on the suitability of the excipients, the characteristics of the extract, and the stability testing method used. This review is expected to serve as a reference in the development of more stable and high-quality natural ingredient extract formulations.